Análise comparativa das concentrações de leptina e adiponectina no líquido folicular de mulheres com diferentes índices de massa corporal submetidas ao tratamento de fertilização in vitro - Souza, Beatriz Zappellini de [UNIFESP] (2018)
The association between obesity and the increased risk of reproductive failure has been related to metabolic and endocrine alterations, and many studies have shown the relevance of nutritional balance and the availability of nutrients in fertility. Some hormones produced by the adipose tissue, such as leptin and adiponectin, can act as modulators in the GnRH secrection, altering the production and liberation of LH and FSH. Aiming to evaluate the effects of obesity on the follicular microenvironment, leptin and adiponectin levels were measured in follicular fluid from infertile patients, as well as its oxidative stress status. For this purpose, follicular fluid samples of 74 patients of different body mass indices were collected after controlled ovarian stimulation for in vitro fertilization treatment. Patients were divided among three groups: eutrophic (18,5 > BMI < 24,9; n=25), overweight (24,9 > BMI < 29,9; n=24) and obese (BMI > 30; n=25). Leptin and adiponectin levels were measured by MAGPIX TM equipment and the lipid peroxidation analysis was measured by TBARS. Obese patients had a significant higher number of oocytes (8,44 ± 5,69; p=0.04), fertilized oocytes (4,96 ±4,00; p=0.045), D2 embryo (4,92 ± 4,23; p=0.041) and poorquality embryo at D3 (3,59 ± 2,25; p=0.037) when compared with the other groups. Considering the analytes measured in the present study, we observed that obese patients showed higher levels of leptin in follicular fluid, in comparison with controls (622,50 ± 1304,84; p=0.019). This study has shown that BMI is related to leptins’ concentration in the follicular fluid of women undergoing in vitro fertilization.